Innovation in Strategies for Faculty Development and Career Advancement: Inovasi Strategi Pembinaan dan Pengembangan Karir Dosen - Nashrullah, Mochamad; Qausya; Nursalim, Mochamad; Budiyanto; Lestari, Gunarti Dwi (Universitas Muhammadiyah Sidoarjo, 2025)
The Minister of Education, Culture, Research, and Technology's Decree Number 384/P/2024 serves as a strategic foundation in the management of functional lecturer positions to support the tridharma of higher education. This policy responds to the need for aligning national regulations by utilizing technology, such as the Integrated Resource Information System (SISTER), to ensure transparency and accountability. Through an ontological, epistemological, and axiological philosophical approach, this policy emphasizes the importance of the presence of lecturers as agents of change, the validity of data-based assessments, and their benefits for institutions and society. Innovative strategies such as competency needs mapping, mentoring, and reward and punishment techniques are integrated to enhance the performance and professionalism of lecturers. With the five-stage Rogers adoption evaluation framework, this policy is designed to ensure adaptive and evidence-based implementation. Overall, this policy provides a new direction in the transformation of higher education in Indonesia, supports the sustainable development of lecturers, and holistically improves the quality of the academic ecosystem. Highlights: Emphasizes data-driven assessments to ensure transparency and accountability. Integrates competency mapping, mentoring, and rewards to boost professionalism. Adopts a five-stage framework for evidence-based and adaptive implementation. Keywords: functional position of lecturers; SISTER; reward and punishment; evaluation; higher education